PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SULAWESI TENGGARA - Novianti, Jihan; Aliddin, Laode Asfahyadin; Masri, Muhamad; Istianandar, Farhan Ramdhani; Nur, Nofal (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2023)
This study aims (1) to determine the effect of competence and work motivation jointly on employee performance (2) to determine the effect of competence on employee performance (3) to determine the effect of work motivation on employee performance The population of this study is employees of the education and culture department southeast Sulawesi province as many as 66 employees. Because the population in the study was limited, all populations were used as respondents whose data were taken based on census techniques. The analysis used is quantitative analysis using Multiple Linear Regression Analysis. The results show that (1) Competence and work motivation simultaneously have a significant positive effect on employee performance (2) Competence does not a significant positive effect on employee performance (3) Work motivation has a significant positive effect on employee performance. employee performance.